Tejano Legacy : Rancheros and Settlers in South Texas, 1734-1900 - Alonzo, Armando C. (Book collections on Project MUSE., 1998)
""Alonzo makes judicious use of census records, tax rolls, and probate records to trace the evolution of Hispanic families who formed this community for more than five generations. ... He forcefully dispels the myth that the area of Texas between San Antonio and the Rio Grande was a 'no man's land' prior to Anglo-American settlement.""--Choice